Superconducting liquid cryogen insulated power cables for medium voltage applications. Issue 1 (1st May 2022) - Lopez, H; Mensah, P; Cheetham, P; Kim, C H; Pamidi, S
Abstract: Liquid Nitrogen (LN2) is used as the cryogen and is part of the dielectric insulation system in most high temperature superconducting (HTS) power cables. However, in electric propulsion systems for transportation, using LN2 is not feasible due to asphyxiation concerns in the event of a leak in a confined space. Gaseous helium (GHe) has been proposed as an alternate cryogen to relieve this asphyxiation concern. GHe has benefits such as a wider operating temperature range and versatility for a centralized cryogenic cooling system for multiple devices which could potentially reduce the overall weight of the superconducting system. The drawback is that GHe has a lower dielectric strength compared to LN2, which limits its use to low-medium voltage applications. A hybrid cryogen HTS cable was proposed using LN2 as the dielectric media and GHe as the cryogen of an HTS cable to solve the limitations and issues associated with each cryogen and explained in this paper. A 1-m prototype cable that used LN2 as the cryogen and dielectric was fabricated and dielectric breakdown measurements were performed on it to establish a baseline on what to be expected from the hybrid cryogen HTS cable.